Effect of nonionic surfactants on the low temperature winterization separation of fatty acid methyl ester mixtures. (15th February 2017) - Abe, Masahiro; Komatsu, Hiroyuki; Yamagiwa, Kazuaki; Tajima, Hideo
Highlights: The separation of a FAME mixture by additive winterization was examined. Sorbitan mono fatty acid esters were selected as additives. Effects of additives were examined near the cloud points of FAME mixtures. The additive changed crystal appearance and improved phase separation performance. The optimum additive concentration was in the range of 0.25–0.50 wt%. Abstract: This work investigated the removal of saturated fatty acid methyl esters (FAMEs) from FAME mixtures by winterization, employing additives as solid–liquid phase separation improvers during the cooling process. Model mixtures were prepared by blending saturated FAMEs (methyl palmitate and methyl stearate) and an unsaturated FAME (methyl oleate). Sorbitan monopalmitate (Span40) and Sorbitan monostearate (Span60) were selected as separation improvers because their molecular structures were close to those of the saturated FAME in the model mixture. These additives were found to improve the solid–liquid phase separation of FAME mixtures. Four different solid phases were observed during winterization, depending on the additive concentration: a solid wax, a solid incorporating small amounts of liquid, a large crystal agglomeration, and a slurry of fine particles. The formation of the large crystal agglomeration made it easier to perform solid–liquid separation via decantation, such that the saturated FAME was readily removed from the liquid phase when employing the optimum additive concentration. When the additive had an equal or longer carbon chain length compared with the saturated FAME, a greater extent of low temperature separation was obtained. These results will be helpful to the future development of the additive winterization process.